Community Development and English Studies Programme in Higher Education: A Partnership for Progress - Dada, Charisa (NIU Journal of Social Sciences, 2025)
Community development refers to the collaboration between universities and local communities to address social, economic, cultural, and environmental challenges. It is a partnership that supports growth and progress, with universities combining academic expertise, research output and student involvement to promote sustainable development within local communities. This paper interrogates this partnership in the context of English Studies and argues that collaboration with community stakeholders can deepen the students' understanding of social dynamics and empower them as agents of change when such opportunities for practical application are made available within the discipline’s curriculum. This paper employs a qualitative research design focusing on students, faculty, and community members.​ The data collection methods are semi-structured interviews, focus group discussions with stakeholders and document analysis of the English studies syllabus as well as the SIWES programme. The data analysis is thematic identifying and analysing patterns and themes within the qualitative data. Findings include the need to integrate community-oriented content as well as SIWES into the English studies curriculum. By engaging in socially relevant projects addressing community needs such as literacy, cultural preservation, and social justice, English Studies students can enhance their academic development, critical thinking, communication skills and employability while making tangible contributions to their communities. However, challenges such as limited resources, faculty training, and sustainability of partnerships remain. The paper contributes to advancement in knowledge, educational planning and development, and effective decision making with the capacity to contribute to community resilience and sustainable development. Keywords: Community development, English Studies, SIWES, Service-learning, Curriculum modification and integration